Kualitas etika terhadap pelayanan publik di Usaha Mikro, Kecil dan Menengah - Mustaqfiroh, Novi Kholifatul (Maliki Interdisciplinary Journal, 2023)
Medium businesses are economic production businesses that are managed independently by individuals or legal entities. All organizations are responsible for providing good service to their clients. By implementing ethics that are appropriate to public services, the quality of public services will improve. By implementing good and correct public service ethics, the quality of service will also increase. The Alfana Mart store is able to implement public service ethics well so that it can improve the quality of service and improve the image of the Alfana Mart store.